How depression, anxiety and stress (mental health) are related to sleep quality during Ramadan fasting among UiTM Seremban 3 Faculty of Sports Science and Recreation students / Khaliq Mohammad Reza ... [et al.]. - Mohammad Reza, Khaliq; Abu Kasim, Nurul Ain; Raja Hussain, Raja Nurul Jannat; Mohamed, Muhamad Noor; Mazaulan, Mardiana; Syed Mud Puad, Sharifah Maimunah; Md Radzi, Noor Azila Azreen; Mohd Saleh, Maisarah; Shari, Maisarah (2024)
One of the five pillars of Islam are to be fasting during the holy month of Ramadan according to the Qur’an. During Ramadan, Muslims avoid all food and drink, smoking and immoral behaviour from dawn until sunset. Numerous studies have documented the different impacts of fasting during Ramadan on sleep quality and mental health. For instance, Muslims rise early to attend the pre-dawn meal known as Suhur and the morning prayer (Fajr). The study examines how sleep quality, depression, anxiety, and stress are related among students while fasting during Ramadan. The participants for this study were 349 students from the Faculty of Sport Science & Recreation UiTM Seremban 3. Its goal is to recognize any alterations in sleep quality throughout this time and how these mental factors come together, possibly impacting overall mental wellness and quality of life. The study employs surveys to collect information from students at UiTM Seremban 3 Faculty of Sport Science and Recreation, with a specific focus on how fasting impacts mental well-being. Pearson correlation coefficient was used to analyse the data obtained. It shows that there is a significant relationship (p < 0.05) between all the variables. However, the result shows that the association of sleep quality between depression (r = 0.173) and anxiety (r = 0.176) had low strength of relationship. While the association of sleep quality between stress (r = 0.342) had moderate strength of relationship.